Expression of peptidylarginine deiminase‐2 and ‐4, citrullinated proteins and anti‐citrullinated protein antibodies in human gingiva. (16th September 2012) - Harvey, G. P.; Fitzsimmons, T. R.; Dhamarpatni, A. A. S. S. K.; Marchant, C.; Haynes, D. R.; Bartold, P. M.
<x xml:space="preserve">Abstract</x> Background and Objective The presence of citrullinated proteins, and peptidylarginine deiminase types ‐2 (PAD‐2) and ‐4 (PAD‐4) in periodontal tissues, determine the presence of anti‐cyclic citrullinated protein antibodies (anti‐CCP) in gingival crevicular fluid (GCF) and compare the expression of these proteins between inflamed and non‐inflamed sites. Material and Methods Tissue sections were stained using antibodies against citrullinated proteins, PAD‐2 and PAD‐4. RT‐PCR was performed to investigate PAD‐2 and PAD‐4 mRNA in inflamed and non‐inflamed gingival tissues. Anti‐CCP antibodies in gingival crevicular fluid were detected by ELISA. Results Citrullinated proteins, PAD‐2 and PAD‐4 were detected in gingiva. There was a correlation between inflammation and expression of these proteins. mRNAs for PAD‐2 and PAD‐4 were detected in both inflamed and non‐inflamed gingival tissues. Antibodies to CCP were found mostly in the GCF of individuals with periodontitis. Conclusion PAD‐2 and PAD‐4 (protein and mRNA) as well as citrullinated proteins are present in inflamed gingiva, and anti‐CCP antibodies can be detected in the GCF of some patients. Tissue expression of citrullinated proteins and PAD increased with the severity of inflammation. The presence of anti‐CCP antibodies in GCF was almost exclusive to a subset of patients with periodontitis. Increased expression of these proteins in inflamed gingiva lends support to the notion that periodontal inflammation contributes to the inflammatory burden in a similar way to rheumatoid arthritis.